Dampak Perpajakan Akibat Perubahan Batubara Menjadi Barang Kena Pajak Berdasarkan Undang-Undang No. 11 Tahun 2020 bagi Pengusaha Batubara (Studi Kasus PT XYZ) - Al Haqi, Muhammad Abyan; Yuniarwati, Yuniarwati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The impact of changing the status of coal to Taxable Goods (BKP) based on Law No. 11 of 2020 and its implications for taxation for companies, with a case study of PT XYZ. The main problem faced is tax disputes due to differences in interpretation regarding the time of delivery of goods that affect the imposition of Value Added Tax (VAT). This study aims to evaluate the problem based on applicable accounting standards and tax regulations and provide recommendations to prevent similar disputes in the future. The research method used is descriptive qualitative with data collection techniques in the form of interviews, participatory observation, and analysis of related documents such as financial statements, tax invoices, and shipping documents. The results show that tax disputes arise due to discrepancies in revenue recognition and transaction recording between companies and tax authorities. PT XYZ should have recognized revenue at the time the Berita Acara Serah Terima (BAST) (also refer to Handover Report or Minutes of Handover) document was issued, which marked the transfer of rights and risks of the goods. In addition, the Input Tax credited before the company was confirmed as a Taxable Entrepreneur (PKP) was not in accordance with tax regulations. The implications of this study highlight the importance of adequate accounting documentation and revenue recognition as per accounting standards to ensure compliance with tax regulations.